2021
DOI: 10.1038/s41598-021-00518-w
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of historical herbarium small RNAs to the reconstruction of a cassava mosaic geminivirus evolutionary history

Abstract: Emerging viral diseases of plants are recognised as a growing threat to global food security. However, little is known about the evolutionary processes and ecological factors underlying the emergence and success of viruses that have caused past epidemics. With technological advances in the field of ancient genomics, it is now possible to sequence historical genomes to provide a better understanding of viral plant disease emergence and pathogen evolutionary history. In this context, herbarium specimens represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Phylogeny reconstruction showed the historical strain to have originated from a secondary diversification area of the pathogen in North America from where one or a few dispersal events caused P. infestans emergence in Europe (Martin et al 2013, Ristaino 2020, Saville et al 2016, Yoshida et al 2014, Yoshida et al 2015, Yoshida et al 2013). Similar studies reconstructing the evolutionary history of crop pathogens from full genomes have been successfully realized on viruses as well (Al Rwahnih et al 2015, Malmstrom et al 2007, Rieux et al 2021, Smith et al 2014). We recently described the history of the local emergence of the bacterial crop pathogen Xanthomonas citri pv.…”
Section: Introductionmentioning
confidence: 77%
“…Phylogeny reconstruction showed the historical strain to have originated from a secondary diversification area of the pathogen in North America from where one or a few dispersal events caused P. infestans emergence in Europe (Martin et al 2013, Ristaino 2020, Saville et al 2016, Yoshida et al 2014, Yoshida et al 2015, Yoshida et al 2013). Similar studies reconstructing the evolutionary history of crop pathogens from full genomes have been successfully realized on viruses as well (Al Rwahnih et al 2015, Malmstrom et al 2007, Rieux et al 2021, Smith et al 2014). We recently described the history of the local emergence of the bacterial crop pathogen Xanthomonas citri pv.…”
Section: Introductionmentioning
confidence: 77%
“…The historical genome of a 90-yr-old ACMV was reconstructed from small RNA sequences in an herbarium specimen (Rieux et al, 2021). Evolutionary divergence times estimated with the historical genome were significantly higher than those estimated without and are more in accord with historical disease records.…”
Section: Cassava Mosaic Viruses and Vectorsmentioning
confidence: 93%
“…Regarding RNA, usually considered as a highly labile molecule rapidly degraded upon cell death, it has been shown that plant virus small RNAs are surprisingly more stable than long RNAs and DNA molecules (Hartung et al, 2015;Rieux et al, 2021;Smith et al, 2014). This property was used by Rieux et al (2021) to assemble a genome of Cassava mosaic virus (ACMV) using small RNAs extracted from a 90 years-old Cassava herbarium plant herbarium samples. Analysis of small RNAs from ancient cellular microorganisms has not yet been reported.…”
Section: Future Prospectsmentioning
confidence: 99%